Hybrid Method dalam Menentukan Rekomendasi Penerima KIP Kuliah - Wina Yusnaeni; Marlina Marlina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2023)
Indonesia Smart Card (KIP) College has been applied by the government in accordance with the instructions of the president where it is expected that with the Kip college students who are not able and graduated college will be able to continue to a higher level of Higher Education. In the selection of candidates for college KIP recipients, they are selected through several criteria ranging from parental work, a parental income, and others. In the selection system, inaccuracies are still founding for Kip college recipients, this is a discrepancy that is entitled and not entitled to receive Kip assistance. The importance of a decision support system that aims to facilitate decision-making. SPK method that can be used there are several methods one of which is a hybrid method. By using a hybrid method with the stages of calculation of the weight of the criteria to determine the consistency of the criteria and obtained an CR value of 0.08, this proves the weight of the criteria used are consistent. Furthermore, the data comparison of criteria and alternatives in the process that will produce data into two types, namely data recommendations Kip college recipients and non-recommendation data.